DISTORSI PASAR: TADLIS ATAU PENIPUAN OLEH PENJUAL KAOS POLOS DI PASAR ELEKTRONIK SHOPEE - Hasibuan, Harits Ar-Royhan; Achiria, Siti; Bakti Nugroho, Moch Rizal Bayu (Universitas Muhammadiyah Prof DR HAMKA, 2024)
This study explains the concept of tadlis (fraudulent misrepresentation) occurring in e-marketplaces, specifically among sellers of plain t-shirts. This is done to ensure that the public is not easily deceived by products sold in online markets. Fraud is more likely to occur in online markets compared to offline markets due to the absence of face-to-face transactions. The research method used in this study is a qualitative approach with a literature review, drawing on various references related to the issue. In addition, observations were made in the Shopee e-marketplace, particularly among plain t-shirt sellers. The author found that the materials sold did not match the descriptions, allowing sellers to sell products at prices below the average market rate. Based on the results of this study, when linked to the theory of market distortion (tadlis), it can be interpreted that distortions in the Shopee e-marketplace, especially in the sale of plain t-shirt products, still occur frequently. This not only harms buyers but also disadvantages other sellers who offer products at average prices and with clear quality. Therefore, as a buyer or consumer, it is important to understand the products being purchased and not be attracted to the low prices offered by sellers in e-marketplaces. This study delivers an important message to increase consumer awareness and educate them about the potential for fraud in online trading, while also encouraging the importance of transparency and honesty in selling on e-marketplaces. Keywords: Market Distortion, e-marketplace, Tadlis, Islamic Economics.